Attitudes of Mass Media Students in Baghdad University toward Marriage (Journal of the College of Education for Women, 2019)
This Study aims at identifying the attitudes of Masses Media students in Baghdad university toward marriage and the differences of this variable according to sex and the grade. The sample consists of (160) male and Females students, where the questionnaire consists of (40) items’ after achieving their reliability and constancy.The results show that the attitudes of the students are Positive, there are no differences in the attitudes toward marriage according to sex variable (males and females) and there are differences in the variable of grade toward marriage for the First Class. In the lights of these results the researcher suggests making improvements in the attitudes toward marriage suiting the social value and customs of Iraqi Society and making another studies about the impacts of another factors relate with attitudes toward marriage.